Design of Catamaran Electric-Powered Glass Bottom Boat as a Tourism Facility for Gili Noko Island - M. Zulfikar Rahmat; Tri Tiyasmihadi; Kharis Abdullah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Gili Noko Island is one of the islands located in the Bawean archipelago, Gresik regency. The beauty of the beaches and underwater scenery on this island often captivates tourists but access to this island is quite limited. This research proposes the design of a tourist boat concept with a glass bottom route from Bawean to Gili Noko. In this research, there were several research design used those were the principal dimension, lines plan, general arrangement, construction calculation, stability analysis, ship motion analysis, and ship comfort. The selection of the engine is based on the calculated power required for the boat's resistance. The chosen engine is an electric propulsion system as a new environmentally friendly alternative. From the technical analysis, the boat's dimensions are found to be Loa: 11.83 m, B: 4.50 m, B1: 0.80 m, H: 1.50 m, T: 0.60 m, Cb: 0.611, and Vs: 7 knots. The engine power is 10.5 HP, and the battery capacity is 840 Ah. The construction calculation reveals that the boat weigths 4.8584 tons. The stability analysis complies with IMO standards, and the motion analysis and ship comfort meet the criteria set by Olson in 1987.